Research Progress of Acupuncture in the Treatment of Post-Stroke Depression - Ren, Bojian; Wang, Hui (Journal of Contemporary Medical Practice, 2024)
Post-stroke depression (PSD) is a prevalent complication in stroke survivors, characterized by persistent mood disorders that hinder rehabilitation and reduce quality of life. This study examines recent scholarly endeavors focusing on acupuncture (AC) as a feasible therapeutic approach for PSD. By analyzing contemporary literature, it elucidates the Traditional Chinese Medicine (TCM) perspective on PSD and evaluates AC's effectiveness. AC stands out as a promising modality of treatment owing to its potency and negligible side effects, with mechanisms including neurotransmitter modulation, neurotrophic factor regulation, neuronal apoptosis inhibition, inflammatory response modulation, and so on. This review offers valuable insights into PSD from a TCM perspective and highlights AC's potential as a therapeutic intervention, contributing to knowledge advancement and informing clinical practice in PSD management.